How does dolomite application affect the greenhouse gases emissions from the terrestrial environment? – A global synthesis. (15th January 2023) - Umair Hassan, Muhammad; Batool, Maria; Hassan Farooq, Taimoor; Saleem Arif, Muhammad; Aamer, Muhammad; Ahmed Waqas, Muhammad; Albasher, Gadah; Sajjad, Maryium; Shakoor, Awais
Highlights: 32 peer-reviewed publications from 1997 to 2020 were used to conduct the meta -analysis. Soil pH and WFPS had a strong impact on GHGs emissions after dolomite (DM) application. The use of DM increased CO2 emissions while decreasing N2 O emissions. Abstract: Global climatic energy balance has been increasingly altered by massive emissions of greenhouse gases (GHGs), such as carbon dioxide (CO2 ), methane (CH4 ), and nitrous oxide (N2 O), leading to a variety of natural disturbances in terrestrial ecosystems. Further, the increasing use of fossil fuels and the looming climate crisis have created an unprecedented urgency for the development of a biobased circular economy. Therefore, production of biofuels from plant biomass is currently seen as a promising source of renewable energy, ensuring sustainable development with minimal carbon footprint. Soil acidification is considered one of the major obstacles to crop production and a significant source of GHGs emissions, especially N2 O, because acidification changes the physicochemical and biochemical properties of the soil. Dolomite (DM) is the most widely used countermeasure to neutralize soil acidity to improve crop productivity and control net fluxes of GHGs. Nevertheless, the extent of GHG emissions following the application of DM under different environmental conditions is still unclear. Therefore, in this context, we conducted a meta-analysis using 32 peer-reviewed publications to determine the effects of DM, climate zones, and soil properties on GHGs emissions. The results of the current meta-analysis show that DM application significantly increased CO2 emissions (30.34 %) and CH4 emissions (4.91 %), but reduced N2 O emissions by 54.88 %. A significant effect of DM (>10 t ha −1 ) on CO2, CH4, and N2 O emissions was also observed. Increasing soil pH increased CO2 and N2 O emissions by 188.34 % and 49.78 %, respectively, while reducing CH4 emissions by 81.94 %. Most importantly, WFPS, soil textural class, soil C:N ratio, and climate zones were identified as key edaphic factors affecting the GHG emissions following the application of DM. Overall, this meta-analysis fills in the gaps regarding the impact of the application of DM on GHGs emissions in different climates, soil properties, and experimental conditions. In summary, a better understanding of the interactions between DM and GHGs flux in the terrestrial ecosystem can be used not only to avert climatic upheaval, but also to better predict these emissions from acidic soils.